Pengaruh Kualitas Produk, Electronic Word of Mouth dan Media Sosial terhadap Kepuasan Konsumen Kemeja Muslim Pria Merek Bababita Bandung - Alvino Daffa Aryaputra; Imas Sukaesih; Tita Safitriawati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to evaluate the extent to which product quality, electronic word of mouth (e-WOM), and social media usage influence customer satisfaction of Bababita brand Muslim men's shirts in Bandung. Problems faced by Bababita include suboptimal social media management and minimal e-WOM activity, which has the potential to reduce customer engagement and satisfaction. The approach used is quantitative with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research sample consisted of 95 respondents who are Bababita consumers, with data collected through a Likert scale questionnaire and analyzed using SmartPLS 4.0 software. The analysis results show that product quality (path coefficient = 0.45), e-WOM (0.30), and social media (0.20) have a positive and significant effect on customer satisfaction. Simultaneously, these three variables explain 68% of the variation in customer satisfaction (R² = 0.68). This study recommends improving product quality, strengthening e-WOM strategies, and optimizing the use of social media to strengthen customer satisfaction and loyalty in the competitive modest fashion industry in Bandung.